Effect of Transaction Security, Reputation, Legality and Ease of Use of Digital Payments - Meilysianawati, Vaya; Utomo, Sugeng Hadi (Jurnal Ekonomi Balance, 2022)
In essence, digital payments or electronic payments are payments made electronically, in electronic payment systems for money storage, money processing is received in the form of digital information and the transfer method is initialized through digital payment instruments. This digital payment is a server-based or chip-based payment. This digital payment has been increasingly used since 2020 until now due to the Covid-19 virus. This study aims to determine the impact of transaction security, reputation, legality and ease of use on digital payments (electronic payments). The research method used is quantitative with multiple linear regression model data analysis methods with SPSS 25 data processing application processing. The data used in this study is primary data from questionnaire collection with a Likert calculation scale with a total of 67 respondents. The results of this study indicate that the transaction security variable and the convenience variable have a positive and significant effect, while the reputation and legality variables have no insignificant but positive effect. Taken together, ease of transaction, reputation, legality and convenience have a positive and significant impact on the use of digital payments (electronic payments).